A Case Study of Consumer Satisfaction of Kentucky Fried Chicken - Pandey, Rudresh; Rao, K.S.; Er, Cha Ching; Kee, Daisy Mui Hung; Chua, Wan Jun; Hon, Hui Shan; Tan, Chong Yi; Tayal, Sakshi; Sariya, Sariya; Narendath, P. (AIBPM Publisher, 2021)
The purpose of this study is to examine consumer satisfaction towards Kentucky Fried Chicken Corporation (KFC). This paper is presenting what are the factors influencing consumer satisfaction. KFC is known as one of the most popular fast-food chains around the world. The findings indicate that the services and products of KFC give a big impact on consumer satisfaction and thus most of the consumers are satisfied with the current services and KFC products.